The Grand Chessboard : American Primacy and its Geostrategic Imperatives - Brzezinski, Zbigniew (New York Basic Books, 2016)
"Brzezinski delivers a vision for American preeminence in the twenty-first century. The task facing the United States, he argues, is to become the sole political arbiter in Eurasian lands and to prevent the emergence of any rival power threatening our material and diplomatic interests. The Eurasian landmass, home to the greatest part of the globe's population, natural resources, and economic activity, is the "grand chessboard" on which America's supremacy will be ratified and challenged in the years to come. In this landmark work of public policy and political science, Brzezinski outlines a groundbreaking and powerful blueprint for America's vital interests in the modern world. In a revised edition with a new epilogue, Brzezinski brings his seminal work up to date with commentary on the latest global developments, including the war in Ukraine, the re-emergence of Russia, and the rise of China."--
Include Maps, Graphs and Index
Keywords: United States -- Geopolitics -- World politics